ARHGAP25: a novel player in the Pathomechanism of allergic contact hypersensitivity - Czárán, Domonkos; Sasvári, Péter; Lőrincz, Kende; Ella, Krisztina; Gellén, Virág; Csépányi-Kömi, Roland (Frontiers in Immunology, 2025)
ObjectiveContact hypersensitivity (CHS), or allergic contact dermatitis (ACD), is an inflammatory skin disorder characterized by an exaggerated allergic reaction to specific haptens. During this delayed-type allergic reaction, the first contact with the allergen initiates the sensitization phase, forming memory T cells. Upon repeated contact with the hapten, the elicitation phase develops, activating mostly macrophages, cytotoxic T cells, and neutrophilic granulocytes. Our group previously demonstrated that the leukocyte-specific GTPase-activating protein ARHGAP25 regulates phagocyte effector functions and is crucial in the pathomechanism of autoantibody-induced arthritis. Here, we investigate its role in the pathogenesis of the more complex inflammatory process of contact hypersensitivity.MethodsFor sensitization, the abdomens of wild-type and ARHGAP25 deficient (KO) mice on a C57BL/6 background, as well as bone marrow chimeric mice, were coated with 3% TNCB (2-chloro-1,3,5-trinitrobenzene) or acetone in the control group. After five days, ears were treated with 1% TNCB for elicitation. Swelling of the ears caused by edema formation was evaluated by measuring the ear thickness. Afterward, ears were harvested, and histological analysis, investigation of leukocyte infiltration, cytokine production, and changes in relevant signaling pathways were carried out. ARHGAP25 expression at the mRNA and protein levels was measured using murine ear and human skin samples.ResultsARHGAP25 expression increased in human patients suffering from contact dermatitis and in contact hypersensitivity induced in mice. Our data suggest that ARHGAP25 expression is infinitesimal in keratinocytes. In the CHS mouse model, the absence of ARHGAP25 mitigated the severity of inflammation in a leukocyte-dependent manner by reducing the infiltration of phagocytes and cytotoxic T cells. ARHGAP25 altered cytokine composition in the sensitization and elicitation phase of the disease. However, this protein did not affect T cell homing and activation in the sensitization phase.ConclusionOur findings suggest that ARHGAP25 is essential in developing contact hypersensitivity by modulating the cytokine environment and leukocyte infiltration. Based on these findings, we propose ARHGAP25 as a promising candidate for future therapeutic approaches and a potential ACD biomarker.